2019
DOI: 10.1080/1828051x.2019.1586456
|View full text |Cite
|
Sign up to set email alerts
|

Association study and expression analysis of GPC1 gene copy number variation in Chinese Datong yak (Bos grunniens) breed

Abstract: Copy number variations (CNVs) can cause radical changes in phenotype variation, gene expression and evolutionary adaptation, through gene dosage effects, disruption of transcript arrangement and regulatory polymorphisms. Therefore, the current study was undertaken to investigate the distribution of glypican1 (GPC1) CNVs in five domestic yak breeds, and their association growth traits and gene expression. The data were analysed using real-time quantitative PCR (qPCR). Loss and normal copy number types had a sig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(5 citation statements)
references
References 84 publications
0
5
0
Order By: Relevance
“…In beef cattle, 17 CNVs were identified to associate with seven different body traits [22]. Moreover, CNVs of ten genes (CYP4A11, GBP2, GPC1, KCNJ12, KLF3, KLF6, LEPR, MAPK10, MICALL2 and MYH3) were identified in correlation with transcript expression levels and growth traits (e.g., body length and body weight) of Chinese domestic cattle in the previous CNV studies [23][24][25][26][27][28][29][30][31][32].…”
Section: Introductionmentioning
confidence: 94%
See 4 more Smart Citations
“…In beef cattle, 17 CNVs were identified to associate with seven different body traits [22]. Moreover, CNVs of ten genes (CYP4A11, GBP2, GPC1, KCNJ12, KLF3, KLF6, LEPR, MAPK10, MICALL2 and MYH3) were identified in correlation with transcript expression levels and growth traits (e.g., body length and body weight) of Chinese domestic cattle in the previous CNV studies [23][24][25][26][27][28][29][30][31][32].…”
Section: Introductionmentioning
confidence: 94%
“…The relative CNV copy numbers were defined by an evaluation of 2 × 2 −∆∆Ct with the average threshold cycles (Ct) in triplicate independent repeats, where ∆Ct = Ct target gene − Ct reference gene following the previous studies [26,30,31,[41][42][43][44][45][46]. The basic transcription factor 3 (BTF3) acted as the internal reference gene following the study of Bickhart et al [43], because neither CNVs nor segmental duplications were observed in BTF3.…”
Section: Identification Of Cnv and Expression Levels For Gbp6mentioning
confidence: 99%
See 3 more Smart Citations